Three Kinds of Rising-Falling Contours in German wh-Questions: Evidence From Form and Function - Zahner-Ritter, Katharina; Einfeldt, Marieke; Wochner, Daniela; James, Angela; Dehé, Nicole; Braun, Bettina (Frontiers in Communication, 2022)
The intonational realization of utterances is generally characterized by regional as well as inter- and intra-speaker variability in f0. Category boundaries thus remain “fuzzy” and it is non-trivial how the (continuous) acoustic space maps onto (discrete) pitch accent categories. We focus on three types of rising-falling contours, which differ in the alignment of L(ow) and H(igh) tones with respect to the stressed syllable. Most of the intonational systems on German have described two rising accent categories, e.g., L+H* and L*+H in the German ToBI system. L+H* has a high-pitched stressed syllable and a low leading tone aligned in the pre-tonic syllable; L*+H a low-pitched stressed syllable and a high trailing tone in the post-tonic syllable. There are indications for the existence of a third category which lies between these two categories, with both L and H aligned within the stressed syllable, henceforth termed (LH)*. In the present paper, we empirically investigate the distinctiveness of three rising-falling contours (L+H*, (LH)*, and L*+H, all with a subsequent low boundary tone) in German wh-questions. We employ an approach that addresses both the form and the function of the contours, also taking regional variation into account. In Experiment 1 (form), we used a delayed imitation paradigm to test whether Northern and Southern German speakers can imitate the three rising-falling contours in wh-questions as distinct contours. In Experiment 2 (function), we used a free association task to investigate whether listeners interpret the pragmatic meaning of the three contours differently. Imitation results showed that German speakers – both from the North and the South – re-produced the three contours. There was a small but significant effect of regional variety such that contours produced by speakers from the North were slightly more distinct than those by speakers from the South. In the association task, listeners from both varieties attributed distinct meanings to the (LH)* accent as opposed to the two ToBI accents L+H* and L*+H. Combined evidence from form and function suggests that three distinct contours can be found in the acoustic and perceptual space of German rising-falling contours.